2018
DOI: 10.1063/1.5017891
|View full text |Cite
|
Sign up to set email alerts
|

Detection of deep-level defects and reduced carrier concentration in Mg-ion-implanted GaN before high-temperature annealing

Abstract: Large electron capture-cross-section of the major nonradiative recombination centers in Mg-doped GaN epilayers grown on a GaN substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
4
11
0
Order By: Relevance
“…This result is in good agreement with the previous report . In addition, this energy level is close to that derived by the simulation of C–V characteristics of the low‐dosage sample in the previous works . The energy position and σ of level A were E C − 0.18 eV and 4.5 × 10 −17 cm 2 for the low‐dosage sample, whereas for high‐dosage sample, E C − 0.19 eV and 8.0 × 10 −17 cm 2 , respectively.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This result is in good agreement with the previous report . In addition, this energy level is close to that derived by the simulation of C–V characteristics of the low‐dosage sample in the previous works . The energy position and σ of level A were E C − 0.18 eV and 4.5 × 10 −17 cm 2 for the low‐dosage sample, whereas for high‐dosage sample, E C − 0.19 eV and 8.0 × 10 −17 cm 2 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…According to the PAS results, the divacancy is the dominant defect in as‐implanted GaN, which is in good agreement with the present result for the high‐dosage sample. In contrast, for the low‐dosage sample, the dominant deep level, B, was detected at E C − 0.83 eV, which is also in good agreement with the previous reports . In the study by Akazawa and Uetake, a possible mechanism was discussed, in which V Ga and V N exist separately in the low‐dosage sample, whereas the divacancy is mainly formed in a sample with a higher dosage.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…15 Furthermore, it was recently reported that at !500 C, the carrier concentration of Mg implanted metal-organic vapor phase epitaxy (MOVPE) GaN recovers to the as-grown levels. 16 In order to identify those defects responsible for compensation, Saarinen et al 17 have shown that V Ga is the main compensating center in N-rich MOCVD GaN. This is also confirmed by theory that predicts a lower formation energy of the single negative charge state of V Ga in N-rich rather than Ga-rich conditions.…”
Section: Resultsmentioning
confidence: 90%